FORMULASI COLD CREAM PROPRANOLOL UNTUK PENGHANTARAN TRANSDERMAL DENGAN BASIS EMULSI YANG MENGANDUNG VCO (VIRGIN COCONUT OIL) - Muji Lestari; Annas Binarjo (Pharmaciana, 2013)
Propanolol is a non-selective beta-blocker that is used widely to overcome cardiovascular disorder. Development of propranolol in transdermal delivery is necessary to avoid the first pass metabolism that reduces the active metabolite up to 15-23% left. This study was objected to determine the effect of VCO (Virgin Coconut Oil) concentration as a base and penetration enhancer of propranolol in the cold cream preparation through rat skin membrane in vitro. Variation concentration of VCO (0%, 14%, 28%, and 42%) was added to propanolol cold cream. Transdermal in vitro study was performed using vertical type diffusion cell with PBS pH 7,4 as receptor media. The temperature was maintained at 35ºC with a constant stirring rate at 300 rpm. The transport was conducted for 8 hours. Flux, efficiency, and lag time were calculated as responses. The results showed that flux at various concentration of VCO (0%, 14%, 28%, 42%) were 12,30; 14,13; 14,52; and 23,06 -1 cm-2 respectively. The transport efficiency were 6,5x10-4; 7,5x10-4; 8,1x10-4; and 1,22x10-3 % cm-2 respectively. The lag time were 1,13; 1,26; 1,11; and 0,92 hours respectively. It can be concluded that the VCO can be used mainly as a base in the preparation of cold cream and can increase percutaneous permeation of propranolol significantly (p <0.05). VCO concentration of 42% has the highest performance.